2018
DOI: 10.1002/aic.16060
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of shale gas transport and production with complex fractures using embedded discrete fracture model

Abstract: The goal of this study is to develop a new model to simulate gas and water transport in shale nanopores and complex fractures. A new gas diffusivity equation was first derived to consider multiple important physical mechanisms such as gas desorption, gas slippage and diffusion, and non-Darcy flow. For complex fractures, a state-of-the-art embedded discrete fracture model (EDFM) was implemented. Numerical model is verified against a commercial reservoir simulator for shale gas simulation with multiple planar fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Understanding the multiphase transport process in microfractures or microchannels is crucial to predict production performance in shale gas reservoirs [1][2][3] as well as control fluid transport in microfluidic devices. 4,5 Gas shale is a complex sedimentary system that is considered to exhibit different storage space types 6,7 and complex fluid transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the multiphase transport process in microfractures or microchannels is crucial to predict production performance in shale gas reservoirs [1][2][3] as well as control fluid transport in microfluidic devices. 4,5 Gas shale is a complex sedimentary system that is considered to exhibit different storage space types 6,7 and complex fluid transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the history matching results with an actual shale-gas well, Yu et al [12] compared the long-term well productivity between simple and complex fracture geometries and found that complex fracture networks can produce 36.4% more gas recovery after 30 years than the simple fractures. Yu et al [13] built a synthetic single shale-gas well model including 11 planar hydraulic fractures and 200 natural fractures. The authors found that the well performance of 200 two-set natural fractures is much better than that of 200 one-set natural fractures due to the formation of a much more complex connected fracture network.…”
Section: Introductionmentioning
confidence: 99%
“…This concept was implemented by Li and Lee [29] to vertical fracture cases and implemented by Moinfar [26] to non-vertical fracture cases, in which the fractures have arbitrary dip and strike angles. Xu [30] and Yu [31] implemented EDFM to some more complex fracture-networks, such as nonplanar shape and variable aperture. Li [32] combined EDFM with DPDK for reservoirs with different scale fractures.…”
Section: Introductionmentioning
confidence: 99%